Peran DPK dalam memoderasi pembiayaan murabahah pada bank umum syariah - Sari, Deny Kurnia; Annisa, Arna Asna (Journal of Accounting and Digital Finance, 2023)
This research aims to determine the effect of non-performing financing, net operating margin and financing-to-deposit ratio on murabahah financing with third-party funds as a moderating variable in Islamic commercial banks in Indonesia. This type of research is quantitative and involves a population of Islamic commercial banks registered with the Financial Services Authority (OJK). Meanwhile, the sample for this research was determined using a purposive sampling method with criteria determined by the researcher so that 60 samples were obtained from 12 Islamic commercial banks in 2016–2020. The type of data used is panel data. The analysis method used is moderated regression analysis (MRA). The research results show that the NPF and NOM variables hurt murabahah financing. Meanwhile, FDR hurts murabahah financing. DPK, as a moderating variable, is able to moderate the relationship between NPF, NOM and FDR variables on murabahah financing with varying results.